KESADARAN DIRI PESERTA DIDIK TERHADAP PERUNDUNGAN BERLATAR BUDAYA DI SMA DAN MA - Yosef; Delvina Faulin (IKIP Siliwangi, 2025)
This study aims to determine the differences in the level of self-awareness of cultural bullying between high school and MA students based on school type and gender. The research approach used was comparative quantitative, with a sample size of 340 students selected through simple random sampling technique from a population of 2,989 students. The sample consisted of 127 students of SMA Negeri 1 Belitang, 85 students of SMA Negeri 1 Buay Madang, and 128 students of MAN 1 OKU Timur. The categorization results showed that 125 students (37%) were in the medium category, 85 students (25%) in the low category, 83 students (24%) in the high category, 24 students (7%) very high, and 23 students (7%) very low. The results of ANOVA and Independent Samples t-test showed that there was no significant difference between SMA and MA students (p = 0.276 > 0.05), nor by gender (p = 0.784 > 0.05). Thus, school type and gender do not have a significant influence on the level of self-awareness in dealing with cultural bullying.